Systematic significance of the Foliar Trichomes in selected Melastoma L. Species from Fraser Hill, Pahang - Zakaria, Siti Maisarah; Che Amri, Che Nurul Aini; Shahari, Rozilawati; Mohd Yunus, Noor Syaheera (Wolters Kluwer - Medknow, 2020)
Background: The foliar trichomes of five selected Melastoma L. species in Fraser Hill, Pahang, that belongs to Melastomataceae family had been studied. These five species namely Melastoma muticum Ridl., Melastoma decemfidum Roxb., Melastoma perakense Ridl., Melastoma sanguineum x malabathricum, and Melastoma malabathricum var. normale. Aims and Objectives: This study aims to investigate the systematic significance of foliar trichomes in the identification and classification of Melastoma species. Materials and Methods: Methods of investigation involved cross‑section using sliding microtomes on petiole and midrib, epidermal peel, and leaf clearing and observation under a light microscope. Result: The investigation showed that the genus of Melastoma seems to have a great variation of foliar trichomes. This present study has reported nonglandular trichomes in all species studied. However, six types of trichomes were discovered which serve as distinct variations of taxonomic values, such as simple multiseriate (short, pointed end), simple multiseriate (long, pointed end), simple multiseriate (short, hooked end), simple multiseriate (long, hooked end), strigose–setose, and scales trichomes. Surprisingly, the presence of simple multiseriate (long, hooked end) trichome only in M. muticum could be a criterion to diagnose the species. Conclusion: In conclusion, the present study revealed that the foliar trichomes possess as systematic significance in the identification and classification of Melastoma either at genus or species level.